Pharmacokinetics-Pharmacodynamics of a Respiratory Syncytial Virus Fusion Inhibitor in the Cotton Rat Model - Rouan, Marie-Claude (American Society for Microbiology (ASM), 2010)
Human respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections in infants, young children, elderly persons, and severely immunocompromised patients. Effective postinfection treatments are not widely available, and currently there is no approved vaccine. TMC353121 is a potent RSV fusion inhibitor in vitro, and its ability to reduce viral loads in vivo was demonstrated in cotton rats following prophylactic intravenous administration. Here, the pharmacokinetics of TMC353121 in the cotton rat, which is semipermissive for RSV replication, were further explored to build a pharmacokinetic-pharmacodynamic (PK-PD) model and to estimate the plasma drug levels needed for significant antiviral efficacy. TMC353121 reduced the viral titers in bronchoalveolar lavage fluid in a dose-dependent manner after a single subcutaneous administration and intranasal RSV inoculation 24 h after compound administration. The viral titer reduction and plasma TMC353121 concentration at the time of RSV inoculation were well described using a simple E(max) model with a maximal viral titer reduction (E(max)) of 1.5 log(10). The plasma drug level required to achieve 50% of the E(max) (200 ng/ml) was much higher than the 50% inhibitory concentration observed in vitro in HeLaM cells (0.07 ng/ml). In conclusion, this simple PK-PD approach may be useful in predicting efficacious exposure levels for future RSV inhibitors.